FEATURES OF THE APPLICATION OF THE MANDALA TECHNIQE IN THE PSYCHOCORRECTION OF EMOTIONAL STATES IN MIGRANT WOMEN - Datsun, Olena; Chernohod, Rada (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article considers one of the actual scientific and practical problems of modern psychological science – the application mandala technique in psychocorrective work with women who became forced refugees due to the war. Peculiarities of the psychological state of the resettled women require the search for new techniques of corrective work, adaptation of existing ones to the conditions of exposure to constant stress factors of war. The purpose of the study: to develop and adapt actual mandala techniques for psychocorrection of emotional sates of migrant women. The following research methods were used to solve the set tasks: analysis of scientific literature; survey; analysis of products of activity of pupils at performance of the developed corrective tasks. Results: based on the study of the emotional states of migrant women, we determined that the majority of women who left Ukraine with their children fell emotional stress continuously through the war in the country, but also because of their own war that is happening inside. To achieve this goal, we developed a series of techniques based on working with the mandala, which were included in the psychocorrective program of working with migrant women. Conclusions: it is empirically confirmed that in the conditions of war, the majority of migrant women need psychological help. The mandala therapy is one of the directions of effective psychocorrective work with the population’s requests to process the traumatic experience of war. The proposed methods can be recommended for use in complex programs of correction in individual and group work